Mathematical Reasoning Ability in Terms of Self-Efficacy in the CORE Learning Model Assisted by Liveworksheet - Frazwanti, Yuni; Isnarto, Isnarto; Hendikawati, Putriaji (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to analyze the quality of the CORE learning model assisted by Liveworksheet and examine the effect of self-efficacy on students' mathematical reasoning. A quantitative method with a posttest-only control group design was used. Instruments included a reasoning test, self-efficacy questionnaire, student response questionnaire, and observation sheet. The sample consisted of eighth-grade students at SMPN 16 Semarang, selected through cluster random sampling. Data analysis involved planning, implementation, evaluation, and simple linear regression. The results showed the CORE model with Liveworksheet was of good quality, and self-efficacy significantly influenced mathematical reasoning, contributing 71.6%. It is recommended that the interactive CORE model be further developed along with differentiated teaching tools to ensure learning becomes more adaptive to students’ needs.